Escola Açaí: uma experiência educacional no interior da Amazônia tocantina - FORTES, Robson Pena (2018)
This paper is a result of the experience of teaching in the Modular Teaching Organization System of the Padre Pedro Municipal School of Primary Education, a riverside area of the municipality of Igarapé-Miri / PA. Based on the empirical perception of the daily life of the school community, it was possible to verify the importance of the açaí culture in the social dynamics of the people living on the banks of rivers, incorporating habits, customs and relations as belonging, identification, economic and labor, and in a very particular way, relationships in the school environment. In this sense, from History classes, I try to understand how açaí can be used as an element of understanding of the past by teachers of History as an essential didactic object to understand the rural school, the society in which we live and the conflicts. established by the construction of the Amazonian identity of Tocantins.